If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3z + 8 = -1 Reorder the terms: 8 + -3z = -1 Solving 8 + -3z = -1 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -3z = -1 + -8 Combine like terms: 8 + -8 = 0 0 + -3z = -1 + -8 -3z = -1 + -8 Combine like terms: -1 + -8 = -9 -3z = -9 Divide each side by '-3'. z = 3 Simplifying z = 3
| e^2x=27 | | -43-3x=9x+21 | | 2(k+3)=10 | | (4x^2-3x)(5x^2-6x+2)= | | 2x=23 | | (3x-5)(3x+5)= | | 2(2b-1)=14 | | (3x^3-4x^2+x-2)-(x^3-5x^2+3x+2)= | | c=10+30 | | c=a+30 | | 8(b-8)= | | 4(w-5)=36 | | 8=-3u-4 | | x+23=0 | | (x^4-5x^3+7x^2-4x+3)(x-3)= | | 5(2x-4)=4(x-8) | | 5x+4=2x+25 | | 3x^2+2y^2-3x+5y=3 | | r^2+12r+32=0 | | 2(t+7)=6(t+3) | | 5(r+4)=-3(r-12) | | x+20=71 | | 8=0.2n | | (6x^4-4x^3-11x^2+3x+2)(3x+1)= | | 2(a+3)=16 | | 1.2x=24 | | 4x+2=3x-5 | | 2(x-2)=-4(x+4) | | 4(x-3)=3(x+1) | | 89-5x=40x+24 | | 2(x-3)=5x-13 | | 5t+12=4t |